Left subclavian artery malperfusion due to thoracic outlet syndrome during total vertebrectomy for invasive lung cancer: a case report. Issue 1 (December 2017) - Mizunoya, Kazuyuki; Ueda, Kentaro; Takeda, Yoshifumi; Takita, Koichi; Morimoto, Yuji
Abstract Thoracic outlet syndrome (TOS) can interrupt blood flow to upper limbs by vascular compression. We report a case of a 52-year-old man who presented left subclavian artery malperfusion due to TOS during total vertebrectomy (Th2–4) in the prone position for invasive lung cancer. At the time of resection of the vertebral bodies, his left radial systolic blood pressure had begun to drop intermittently and we noticed an interarm pressure difference. Accordingly, we began to monitor the right radial artery pressure and found that only the left radial artery pressure decreased as a result of compressive force from the surgical site. The operation was continued with intermittent malperfusion of the left arm, and when it was prolonged, we asked the surgeons to release the compression. No symptoms of ischemia or nerve injuries in the left arm were observed after the surgery. Retrospective review of his preoperative enhanced computed tomography images suggested a slightly compressed left subclavian artery in the costoclavicular space. Combination of the prone position and a specific upper limb position may be a risk factor for intraoperative TOS. An interarm blood pressure difference is a clue to detect accidental arterial TOS during general anesthesia.